A Case for Ethical Veganism: Intuitive and methodological considerations - McPherson, Tristram (2014)
This paper argues for ethical veganism: the thesis that it is typically wrong to consume animal products. The paper first sets out an intuitive case for this thesis that begins with the intuitive claim that it is wrong to set fire to a cat. I then raise a methodological challenge: this is an intuitive argument for a revisionary conclusion. Even if we grant that we cannot both believe that it is permissible to drink milk, and that it is wrong to set fire to cats, this leaves open the question of which of these judgments we should abandon. I consider and reject three strategies for addressing this question: more methodologically naïve moral theorizing, appeal to systematic normative theory, and attacking non-moral presuppositions. I argue that philosophically satisfying the resolution of the conflict requires debunking our grounds for belief in one of the conflicting claims. Finally, I argue that ethical veganism is supported by consideration of the most salient debunking arguments available.
Keywords: Veganism; methodology in ethics; Applied Ethics; animal ethics